Effects of simulated acid rain on germination, seedling growth and oxidative metabolism of recalcitrant‐seeded Trichilia dregeana grown in its natural seed bank. Issue 1 (27th June 2014) - Ramlall, Chandika; Varghese, Boby; Ramdhani, Syd; Pammenter, Norman W.; Bhatt, Arvind; Berjak, Patricia; Sershen
<x xml:space="preserve">Abstract</x> Increased air pollution in a number of developing African countries, together with the reports of vegetation damage typically associated with acid precipitation in commercial forests in South Africa, has raised concerns over the potential impacts of acid rain on natural vegetation in these countries. Recalcitrant (i.e. desiccation sensitive) seeds of many indigenous African species, e.g. must germinate shortly after shedding and hence, may not be able to avoid exposure to acid rain in polluted areas. This study investigated the effects of simulated acid rain (rainwater with pH adjusted to pH 3.0 and 4.5 with 70:30, H2SO4:HNO3) on germination, seedling growth and oxidative metabolism in a recalcitrant‐seeded African tree species Trichilia dregeana Sond., growing in its natural seed bank. The results suggest that acid rain did not compromise T. dregeana seed germination and seedling establishment significantly, relative to the control (non‐acidified rainwater). However, pH 3.0 treated seedlings exhibited signs of stress typically associated with acid rain: leaf tip necrosis, abnormal bilobed leaf tips, leaf necrotic spots and chlorosis, reduced leaf chlorophyll concentration, increased stomatal density and indications of oxidative stress. This may explain why total and root biomass of pH 3.0 treated seedlings were significantly lower than the control. Acid rain also induced changes in the species composition and relative abundance of the different life forms emerging from T. dregeana's natural seed bank and in this way could indirectly impact on T. dregeana seedling establishment success.